PENGARUH JENIS PUPUK DAUN DAN JENIS MULSA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAYAM MERAH (Amaranthus tricolor L.) VARIETAS BISI - Nurmas, Andi; Fitriah, Sitti Putri (Jurnal Agroteknos, 2011)
ABSTRACTThe objective of this experiment was to study the effect of foliar fertilizer type and mulch type on the growth and production of red spinach (Amaranthus tricolor L.) bisi variety. The experiment was conducted from July to September 2010 in the Village District Padaleu Poasia Kendari. The research was based on randomized block design (RBD) in the factorial pattern consisting of two factors, with three replications. The first factor was the type of foliar fertilizer which consisted of 4 levels: without foliar fertilizer (K0), Gandasil-D (K1), Bayfolan (K2), Seprint (K3). The second factor was the type of mulch which consisted of 3 types, namely: no mulch (M0), plastic black silver mulch (M1), and reed leaves (M2). The results showed that in general the interaction between foliar fertilizer of Bayfolan and plastic mulch (MPHP) gave a significant effect on the growth and yield of red spinach (Amaranthus tricolor L.) bisi variety. Keywords : Red Spinach, Foliar Fertilization Mulch